THE COME BACK OF THE FORGOTTEN HEROES: A NEW INTERPRETATION OF LITERARY AND HISTORICAL NARRATIVES ABOUT THE WARS ON THE STEPPE BORDER OF UKRAINE IN THE 16TH – MID-17TH CENTURIES (peer-review on the monograph: Vyrsky D. The War in the South: Chronicles of the Steppe Borderland of Ukraine (the 16th – Mid-17th Centuries). Kyiv: Institute of History of Ukraine, NAS of Ukraine, 2024. 292 p.) - MYKYTYUK , Volodymyr; NEVMERZHYTSKA, Olena (EAST EUROPEAN HISTORICAL BULLETIN, 2025)
peer-review on the monograph: Vyrsky D. The War in the South: Chronicles of the Steppe Borderland of Ukraine (the 16th – Mid-17th Centuries). Kyiv: Institute of History of Ukraine, NAS of Ukraine, 2024. 292 p.)